Moving towards critical AI literacy in LIS education: a scoping review and syllabi analysis. - Bridges, Laurie; Lopezosa, Carlos; Centelles Velilla, Miquel; Ferran-Ferrer, Núria (Electronic Library, 2025)
Purpose: The purpose of this study is to investigate generative artificial intelligence (AI) literacy integration within library and information science (LIS) educational programs, examining how academic curricula prepare future professionals to engage critically and competently with AI technologies. Design/methodology/approach: A dual methodological approach combining a systematic scoping review of AI literature in LIS and a detailed analysis of syllabi from leading international LIS programs is used. The review identifies emerging trends and frameworks, while the syllabi analysis examines practical implementation. Findings: The investigation reveals significant pedagogical fragmentation and global inequities in the integration of AI literacy in LIS programs, characterized by a lack of consensus around the frameworks used, institutional disparities and false dichotomies between technical and critical pedagogies. Research limitations/implications: This study highlights the risks of stratification, where some programs offer sophisticated interdisciplinary training, while others provide only technical instruction, potentially fragmenting the global LIS community, at a time when coordinated responses to AI's implications are crucial. Practical implications: While many programs have implemented basic AI literacy, there is uneven global integration of critical AI literacy, which more closely aligns with the profession's values of social justice and democratic well-being (ALA, 2023; IFLA, 2025). Social implications: Research addresses the profession's obligation to serve as ethical information stewards in an algorithmic age, emphasizing that graduates must leverage AI capabilities while critically examining implications for information equity, privacy and democratic participation (ALA, 2023; IFLA, 2025). Originality/value: This research bridges the gap between conceptual developments in LIS research and practical educational implementation, providing the first comprehensive analysis of AI literacy operationalization across international LIS curricula.